Influence of Heat Flux and Friction Coefficient on Thermal Stresses in Risers of Drum Boilers under Dynamic Conditions of Steam Demand. (17th November 2013) - Habib, M. A.; Alzaharnah, I.; El-Shafei, M.; Merah, N.; Al-Anizi, S.; Al-Awwad, M. Y.; Hajji, M.
Abstract : Boiler swing rate, which is the rate at which the boiler load is changed, has significant influence on the parameters of the boiler operating conditions such as drum water pressure and level, steam quality in the riser tubes, wall temperatures of riser tubes, and the associated thermal stresses. In this paper, the thermal stresses developed in boiler tubes due to elevated rates of heat transfer and friction are presented versus thermal stresses developed in tubes operated under normal conditions. The differential equations comprising the nonlinear model and governing the flow inside the boiler tubes were formulated to study different operational scenarios in terms of resulting dynamic response of critical variables. The experimental results and field data were obtained to validate the present nonlinear dynamic model. The calculations of the heat flux and the allowable steam quality were used to determine the maximum boiler swing rates at different conditions of riser tube of friction factor and heat flux. Diagrams for the influence of friction factor of the boiler tubes and the heat flux, that the tube is subjected to, on the maximum swing rate were examined.